2023
DOI: 10.1002/dmrr.3605
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy relates to the incidence of foot ulcers and amputations in type 2 diabetes

Abstract: Aims We investigated whether Diabetic Retinopathy (DR) is related to Diabetic Foot Ulcer (DFU) development, adjusted for the stratification of the International Work Group on Diabetic Foot (IWGDF) guidance. Materials and Methods DR and IWGDF stratification was registered retrospectively in patients hospitalised from 2009 to 2017 for uncontrolled and/or complicated type 2 diabetes. New DFUs were registered until 2020. Survival analyses categorised the subjects for DR, and multivariate Cox regression adjusted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
(75 reference statements)
2
3
0
Order By: Relevance
“…9 Both DR and DFU are closely associated microvascular complications of DM. Research has shown that there is a positive correlation between the incidence of DFU and DR. 10,18 The results of a study published by Gu et al indicated that microvascular disease in diabetes is positively correlated with the occurrence of DFU, and the risk of DFU in patients with diabetes and DR is significantly increased, which is consistent with the findings of this study. 25 The present study shows that DR can significantly increase the incidence of DFU.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…9 Both DR and DFU are closely associated microvascular complications of DM. Research has shown that there is a positive correlation between the incidence of DFU and DR. 10,18 The results of a study published by Gu et al indicated that microvascular disease in diabetes is positively correlated with the occurrence of DFU, and the risk of DFU in patients with diabetes and DR is significantly increased, which is consistent with the findings of this study. 25 The present study shows that DR can significantly increase the incidence of DFU.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the titles and abstracts, 331 irrelevant articles were excluded, leaving 96 articles. After reading the full text and applying the inclusion and exclusion criteria, 11 articles were finally included with a total of 10 208 patients, including 2191 in the DFU group and 8017 in the non‐DFU group 9–19 . The screening process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(16) Likewise, a study conducted in 522 patients found a relationship (HR: 3.56, 95%CI: 1.26-10.07) between diabetic retinopathy and amputations. (17) These results are similar to those obtained in several studies (18,19).…”
Section: Discussionsupporting
confidence: 91%
“…The chronic and refractory skin injuries such as diabetes foot ulcers (DFU) have become a health problem affecting the diabetes patients life quality [18]. Prevention and treatment of DFU is a multidisciplinary process [19].…”
Section: Discussionmentioning
confidence: 99%